Project Charter, Scope, and Time Management In the Movie Industry - Hellas, Markus (My University, 2015)
This thesis explores how the project charter development, project scope management, and project time management are executed in a Finnish movie production. The deviations and analogies between a case movie production and best practices suggested in PMBOK are presented. Empirical material from the case is gathered with two semi-structured interviews with a producer and a line producer. The interview data is categorized according to PMBOK knowledge areas. The analysis is complemented with movie industry specific norms found in popular movie production guides. The described and observed methods are linked together and the relationship between them is discussed. The project charter development, which is referred as a green light process in the movie industry, is mostly analogous between all areas. The deviations are in the level of formality. The green lighting in the case movie was accomplished without bureaucratic reports described in movie production guides. The empirical material shows that project management conventions and movie industry employ similar methods especially in scope management. Project management practices introduce a work breakdown structure (WBS) method, and movie production accomplishes the same task by developing a shooting script. Time management of the case movie deviates on most parts from the methods suggested in PMBOK. The major deviation is resource management. PMBOK suggests creating a resource breakdown structure. The case movie production accomplished this through budgeting process. Furthermore the popular movie production guides also disregard resource management as sovereign process. However the activity listing is quite analogous between the case movie and PMBOK. The final key observation is that although there is a broad set of effective and detailed movie industry specific methods, a comprehensive methodology that would cover the whole production process, such as Prince2 or Scrum, seems to be missing from the movie industry.